TARI LEGONG KERATON DI DESA PEKRAMAN SUKAWATI DALAM PENCIPTAAN SENI LUKIS - Antara, I Made Gita Teja; Rinu, Ni Made; Gunawan, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2021)
The Legong Keraton dance has the meaning of a classical dance from the island of Bali which has agile, flexible and smooth movements because it is danced by three girls aged 10-12 years, and is accompanied by the gamelan Gong Kebyar. This dance functions as a balih-balihan dance or entertainment. Many stories are played in the performance of the Legong Keraton dance, one of the most popular stories is Lasem which tells the love of Prabu Lasem to Putri Rankesari. There are 5 structures in the performance of this dance which include papeson, pangawak, penyet, pengipuk and pakahad. This dance, which was originally a dance of entertainment for kings and nobles in a palace or castle. The method used in the research of Legong Keratondi Dance in Pekraman Village, Sukawati, is the method of observation, interviews, literature, and documentation. The data analysis method used is a qualitative method. The theories used to support the creation of works are the theory of painting, aesthetic theory, and semiotic theory, using the flow of naturalism.